(untitled) (Journal of Applied Learning and Teaching, 2023)
In this study, observed for malpractice behaviour under three forms of sitting arrangement. The aim was to identify the conditions under which test-takers are more likely to engage in different forms of examination malpractice. The study was primarily concerned with providing answers to four research questions and testing four null hypotheses. Data were collected using an observation checklist conceived by the researchers. Data analysis was done using frequency counts, simple percentages and the Chi-square test of independence. It was determined, among other things, that many higher education test-takers participated in various forms of examination misconduct. Giraffing, copying from colleagues, script exchange, discussion with peers, using small papers containing answers, using phones, swaying seats, handwriting on desks, using headphones with recorded audio, and requesting invigilators for help are all manifestations of these behaviours. It was found that test-takers malpractice behaviour varied with the sitting arrangement used. Furthermore, the malpractice behaviours exhibited and the instances of cheating were not significantly dependent on gender, although males exhibited, on average, a higher rate of malpractice behaviours. However, students’ malpractice behaviours and the instances of cheating significantly depended on the sitting arrangement implemented. The educational assessment implications were examined considering these findings. Examiners wishing to limit examination fraud and improve efficient performance assessments may utilise one or more combinations of gender separation and inter-class test sitting arrangements.